The Effect Of Compliance On A Low Salt Diet On Blood Pressure In Hypertension Patients Treatment In Grandmed Hospital Lubuk Pakam - Ginting, Wira Maria; Aulia, Annisa (Jurnal EduHealth, 2022)
Hypertension is an increase in blood pressure beyond normal limits with a diastolic pressure of 90 mmHg or a systolic pressure of 140 mmHg. Hypertension is a disease that cannot be cured but can be controlled, one of which is with a low-salt diet. Adherence in undergoing a low-salt diet is the main key to the recovery of hypertensive patients. When hypertension is not controlled will appear complications in the organs. To prevent blood pressure, exercise regularly, maintain an ideal weight, consume healthy foods, manage stress, and get enough sleep. Checkan blood pressure periodically to the doctor, The purpose of this study is to analyze the effect of adherence to a low-salt diet on the blood pressure of hypertensive patients. This study used a total sampling method, namely sampling techniques where the number of samples was equal to the population, the sample in this study was 15 inpatient hypertension patients at GrandMed Lubuk Pakam Hospital. Research shows that female respondents were 7 people (46.7%) male respondents as many as 8 people (53.3%). This study can be seen that from 15 respondents, it can be seen that 11 patients who adhered to a low-salt diet adhered to (73.3%), and patients who did not comply with a low-salt diet adherence were 4 people (2 6.7%). This study is a Cross sectional study as many as 15 respondents were the subject of this study. The results of statistical tests showed that there was an effect of adherence to a low-salt diet on blood pressure in inpatient hypertensive patients at Grandmed Lubuk Pakam Hospital with values (p Value = 0.000). Thus it can be concluded that there is an effect of adherence to a low-salt diet on inpatients at GrandMed Lubuk Pakam hospital.